A non-parametric test for independence of time to failure and cause of failure for discrete competing risks data. Issue 5 (3rd September 2021) - Sreedevi, E. P.; Kattumannil, Sudheesh K.; Dewan, Isha
Abstract : Competing risks data with discrete lifetime come up in practice. However, only limited literature exists for such data. In this paper, we propose a non-parametric test based on U -statistics for testing independence of time to failure and cause of failure of competing risks data when the lifetime is a discrete random variable. Asymptotic distribution of the proposed test statistic is derived. An extensive Monte Carlo simulation study is conducted to assess the finite sample performance of the proposed test. The flexibility of the testing procedure is illustrated using real data sets on oral cancer patients and drug-exposed pregnancies.